2020
DOI: 10.1002/hed.26484
|View full text |Cite
|
Sign up to set email alerts
|

Association between external and internal lymphedema and chronic dysphagia following head and neck cancer treatment

Abstract: Background: To examine the relationship between chronic external and internal head and neck lymphedema (HNL) and swallowing function in patients following head and neck cancer (HNC) treatment. Methods: Seventy-nine participants, 1-3 years post treatment were assessed for external HNL using the MD Anderson Cancer Centre Lymphedema Rating Scale, and internal HNL using Patterson's Radiotherapy Edema Rating Scale. Swallowing was assessed via instrumental, clinical and patient-reported outcome measures. Results: HN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Time was the only factor found to independently predict edema, with increased edema of the posterior pharyngeal wall noted post‐CRT. The lack of significant findings correlating edema with patient perception and swallow function was surprising, given previous studies which have shown such correlations, using subjective measures of internal edema . It should be noted, however, that both of these prior studies were conducted on patients >3 months post‐CRT; a time when the acute effects of radiation such as mucositis and radiation dermatitis, which cause pain, excessive mucous production, and xerostomia, would have likely subsided .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Time was the only factor found to independently predict edema, with increased edema of the posterior pharyngeal wall noted post‐CRT. The lack of significant findings correlating edema with patient perception and swallow function was surprising, given previous studies which have shown such correlations, using subjective measures of internal edema . It should be noted, however, that both of these prior studies were conducted on patients >3 months post‐CRT; a time when the acute effects of radiation such as mucositis and radiation dermatitis, which cause pain, excessive mucous production, and xerostomia, would have likely subsided .…”
Section: Discussionmentioning
confidence: 97%
“…Intra‐rater reliability of this scale is reported to range from “fair” to “good”, and the authors suggest that reliability may be improved upon by using a pre‐post study design with the patient serving as their own control. Using this subjective scale, Jeans and colleagues noted a correlation between internal edema and qualitative patient reports of swallowing difficulty, including “tightness” . Jackson et al found significant positive correlations between severity of edema of pharyngeal and laryngeal structures and functional swallowing outcomes as indicated by scores on the Dysphagia Outcome and Severity Scale (DOSS) and the National Outcomes Measurement System (NOMS) …”
Section: Introductionmentioning
confidence: 99%
“…Among HNC patients, external lymphedema manifests as soft tissue swelling while internal lymphedema affects the mucosal‐lined structures of the aerodigestive tract. Both internal and external lymphedema is associated with greater patient perception of dysphagia, laryngeal penetration/aspiration, and diet modification 148,149 . Preliminary studies suggest that manual lymph drainage, combined with stretching and swallowing exercises, may improve lymphedema and dysphagia symptoms in HNC survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Both internal and external lymphedema is associated with greater patient perception of dysphagia, laryngeal penetration/ aspiration, and diet modification. 148,149 Preliminary studies suggest that manual lymph drainage, combined with stretching and swallowing exercises, may improve lymphedema and dysphagia symptoms in HNC survivors. Although prospective studies defining best practices for the management of lymphedema and dysphagia related to internal lymphedema are lacking, 150 there was strong consensus among panel members that lymphedema therapy contributes to improved swallowing in HNC patients with lymphedema (Table 5; Statement 52).…”
Section: Lymphedema Therapymentioning
confidence: 99%
“…Furthermore, the scale was only tested using speech and language therapists highly experienced in conducting nasoendoscopy, thus limiting generalisability to a wider population of raters such as surgical and radiation oncologists who regularly perform endoscopy on these patients. Since then, other research groups have reported interrater reliability co-efficients ranging from low levels of agreement for the valleculae (weighted Kappa = 0.08) 10 to excellent agreement for the arytenoids (Intraclass Correlation Coefficient = 0.89) 11 (see Supplementary Table S1). The purpose of this study was to revise the existing Patterson Edema Scale to improve its reliability and utility and to determine whether it can be reliably used across disciplines.…”
Section: Introductionmentioning
confidence: 99%